Patriarchy, Women’s Empowerment And Social Capital - Hanzen, Marcia; Coltre, Sandra Maria (Seven Editora, 2023)
This article is part of the dissertation entitled "Root of Swidden: Female empowerment and social capital in family agriculture", defended in the Graduate Program in Sustainable Rural Development, which sought to study the relationship between the seizure of social capital and the female empowerment of women farmers belonging to AAFEMED – Association of Family farmers and Agroecological Farmers of Medianeira/PR. The methodology for creating a conceptual map correlating the two themes was bibliographic research. The conceptual map is a model for application in field research, and can be complemented from new views on indicators of empowerment and social capital. DOI: https://doi.org/10.56238/methofocusinterv1-099